Juridical Review of Trade Secret Violations in Franchise Business Activities with Case Study of Decision No.413/Pdt.G/2014/PN.Jkt.Utr - Adrian Ali Akhbar Adrian (Fakultas Hukum Universitas Hang Tuah, 2021)
Many companies engaged in various industrial fields carry out business activities using the franchise business method. In running a franchise business, the brand owner or the Franchisor grants the right to the Franchisee, either an individual or a company, to carry out business activities by utilizing intellectual property rights in the form of a brand, name, system, procedure, or trade secret belonging to the Franchise grantor (Franchisor) in limited capacity under the franchise agreement. The purpose of this paper is to analyze the legal protection of trade secrets and dispute resolution against trade secret violations. The writing of this journal uses juridical-normative as a type of legal research using several approaches, i.e., legislation, conceptual and case. The analysis results show that legal protection of trade secrets is obtained as long as the information is kept confidential and has economic value, and there is a license agreement for franchise business activities. On the other hand, related to dispute resolution regarding trade secret violations, it can be resolved based on an agreement between the two parties related to the choice of law and place to resolve occurring disputes